A-FABP and oestrogens are independently involved in the development of breast cancer. (2nd January 2019) - Li, Bing; Hao, Jiaqing; Yan, Xiaofang; Kong, Maiying; Sauter, Edward R.
ABSTRACT: We previously reported that postmenopausal obese women exhibit increased levels of circulating adipocyte fatty acid binding protein (A-FABP), which is associated with breast cancer (BC) development. In postmenopause, increased oestrogen levels are reported to be associated with increased BC risk. Herein, we assessed if oestrogens, including oestrone (E1), oestradiol (E2) and oestriol (E3), are associated with A-FABP in the obesity-related BC development. We collected 249 serum samples from women with or without BC and measured serum levels of E1, E2, E3 and A-FABP. Considering all subjects, E1 and E2 but not E3 levels were significantly higher in pre- than in postmenopause individuals. E3 and E1 levels were higher in non-obese than in obese women. When samples were separated by BC status, E2 levels were significantly higher, while E1 and E3 levels were significantly lower in postmenopausal obese than non-obese women without BC. These differences based on body mass index (BMI) were not observed among women with BC. E3 levels were higher in obese women with BC than those without. A-FABP levels were significantly higher in postmenopausal obese women regardless of BC status. In addition, A-FABP was not associated with E1, E2 or E3. Altogether, our data suggest that A-FABP is independently regulated by obesity and menopausal status compared to oestrogens, thus playing a unique role in the development of BC.